Mansonia spp. population genetics based on mitochondrion whole-genome sequencing alongside the Madeira River near Porto Velho, Rondonia, Brazil - Alonso, Diego Peres [UNESP]; Alvarez, Marcus Vinicius Niz [UNESP]; Amorim, Jandui Almeida; de Sá, Ivy Luizi Rodrigues; de Carvalho, Dario Pires; Ribeiro, Kaio Augusto Nabas; Ribolla, Paulo Eduardo Martins [UNESP]; Sallum, Maria Anice Mureb (Elsevier, 2022)
In high abundance, females of the genus Mansonia (Blanchard) can be a nuisance to humans and animals because they are voraciously hematophagous and feed on the blood of a myriad of vertebrates. The spatial-temporal distribution pattern of Mansonia species is associated with the presence of their host plants, usually Eichhornia crassipes, E. azurea, Ceratopteris pteridoides, Limnobium laevigatum, Pistia stratiotes, and Salvinia sp. Despite their importance, there is a lack of investigation on the dispersion and population genetics of Mansonia species. Such studies are pivotal to evaluating the genetic structuring, which ultimately reflects populational expansion-retraction patterns and dispersal dynamics of the mosquito, particularly in areas with a history of recent introduction and establishment. The knowledge obtained could lead to better understanding of how anthropogenic changes to the environment can modulate the population structure of Mansonia species, which in turn impacts mosquito population density, disturbance to humans and domestic animals, and putative vector-borne disease transmission patterns. In this study, we present an Illumina NGS sequencing protocol to obtain whole-mitogenome sequences of Mansonia spp. to assess the microgeographic genetic diversity and dispersion of field-collected adults. The specimens were collected in rural environments in the vicinities of the Santo Antônio Energia (SAE) hydroelectric reservoir on the Madeira River.
Keywords: Mansonia spp.; Mitogenome; NGS low density sequencing; Population genetics; SNP markers